Quantum Machine Learning Untuk Prediksi Emisi Gas Rumah Kaca dalam Perspektif Filsafat Sains : Quantum Machine Learning for Predicting Greenhouse Gas Emissions from a Philosophy of Science Perspective - Hidayat, Wahyu; Surendro, Kridanto; Mahayana, Dimitri; Rosmansyah, Yusep (Undiksha, 2024)
The climate change issues due to greenhouse gas emissions and the emergence of Quantum Machine Learning technology have sparked various studies in utilizing quantum machine learning (QML) to predict greenhouse gas emissions (GHG). This article aims to illustrate research related to the implementation of QML for GHG emission prediction from the perspective of the philosophy of science, particularly in terms of the scientific revolution from Thomas Kuhn's perspective, research program analysis from Imre Lakatos' perspective, pseudoscience pitfalls, potential biases of injustice, ethical and moral aspects, and their impact on society. The article is structured using a qualitative descriptive method. Reference sources include original articles and review articles from journals collected from the Scopus database with topics related to GHG emission prediction. Based on the review of the articles, it can be outlined that research on QML for GHG emission prediction is a progressive science currently in the phase of intensive exploration and development, where the research paradigm in this area is dominated by logical positivism and pragmatism. However, over time and with the development of the research context, new paradigms may emerge as additions or even replace existing research paradigms. The article also identifies the potential biases of injustice, ethical and moral aspects, and the impact of research in this field on society, recommending five strategies to avoid pseudoscience pitfalls related to research on QML for GHG emission prediction.